Revisiting the oldest manure of India, Kunapajala: Assessment of its animal waste recycling potential as a source of plant biostimulant - Mukherjee, Shibasis; Basak, Ayanita; Chakraborty, Argha; Goswami, Rupak; Ray, Krishnendu; Ali, Md. Nasim; Santra, Sayantan; Hazra, Alok Kumar; Tripathi, Sudipta; Banerjee, Hirak; Layek, Jayanta; Panwar, Azad S.; et al. (Frontiers in Sustainable Food Systems, 2023)
India's oldest documented manure, most commonly referred to as Kunapajala, has a long history of over 1,000 years in crop cultivation. Kunapajala is primarily an in-situ decomposition technology of animal waste and can potentially provide an eco-friendly pipeline for recycling bio-waste into essential plant nutrients. This traditional animal manure, in addition, also contains dairy excreta (e.g., feces and urine), dairy products (e.g., milk and ghee), natural resources (e.g., honey), broken seeds or grains, and their non-edible by-product waste. Here, we aimed to assess the waste recycling and plant biostimulant potential of Kunapajala prepared from livestock (e.g., Black Bengal goats) or fish (e.g., Bombay duck) post-processed wastes over different decomposition periods, e.g., (0, 30, 60, and 90-days). In this study, an in-situ quantification of livestock- (lKPJ) and fish-based Kunapajala (fKPJ) reveals a dynamic landscape of essential plant primary nutrients, e.g., (0.70 > NH4-N < 3.40 g•L−1), (100.00 > P2O5 < 620.00 mg•L−1), and (175.00 > K2O < 340.00 mg•L−1), including other physico-chemical attributes of Kunapajala. Using correlation statistics, we find that the plant-available nutrient content of Kunapajala depicts a significant (p < 0.0001) transformation over decomposition along with microbial dynamics, abundance, and diversities, delineating a microbial interface to animal waste decomposition and plant growth promotion. Importantly, this study also reports the indole 3-acetic acid (IAA) content (40.00 > IAA < 135.00 mg•L−1) in Kunapajala. Furthermore, the bacterial screening based on plant growth-promoting traits and their functional analyses elucidate the mechanism of the plant biostimulant potential of Kunapajala. This assay finally reports two best-performing plant growth-promoting bacteria (e.g., Pseudomonas chlororaphis and Bacillus subtilis) by the 16S ribotyping method. In support, in-planta experiments have demonstrated, in detail, the bio-stimulative effects of Kunapajala, including these two bacterial isolates alone or in combination, on seed germination, root-shoot length, and other important agronomic, physio-biochemical traits in rice. Together, our findings establish that Kunapajala can be recommended as a source of plant biostimulant to improve crop quality traits in rice. Overall, this work highlights Kunapajala, for the first time, as a promising low-cost microbial technology that can serve a dual function of animal waste recycling and plant nutrient recovery to promote sustainable intensification in agroecosystems.